2014
DOI: 10.1177/0954406213519758
|View full text |Cite
|
Sign up to set email alerts
|

An approach to evaluating product assembly precision considering the effect of joint surface deformation

Abstract: This paper proposes an approach to evaluating the product assembly precision in different assembly sequences, considering the effect of joint surface deformation. Three assembly variation sources, including manufacturing variation, assembly clearance and joint surface deformation, which have effect on the final assembly precision are analyzed. Based on finite element analysis, a hybrid genetic algorithm and back-propagation neural network model is built to predict the assembly variations, which are caused by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Jayaprakash et al (2014) developed a FEM model for a motor assembly to determine the deformation of various parts due to the influence of inertia effects and temperature change and integrated the deformations into tolerance design. Lu and Wang (2014) proposed an approach to evaluating the product assembly precision in different assembly sequences, considering the effect of joint surface deformation under different assembly conditions and different parameters of the joint surface based on finite element analysis. Guo et al (2016) proposed a method using FEM to calculate the assembly variation propagation of 3D assemblies considering geometric variation and part deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Jayaprakash et al (2014) developed a FEM model for a motor assembly to determine the deformation of various parts due to the influence of inertia effects and temperature change and integrated the deformations into tolerance design. Lu and Wang (2014) proposed an approach to evaluating the product assembly precision in different assembly sequences, considering the effect of joint surface deformation under different assembly conditions and different parameters of the joint surface based on finite element analysis. Guo et al (2016) proposed a method using FEM to calculate the assembly variation propagation of 3D assemblies considering geometric variation and part deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the accuracy of this model was demonstrated with a panel through the finite element analysis. Lu and Wang 25 considered the deformation of the joint surface in different assembly sequences, and proposed a method to evaluate the assembly quality of the product. It was found that the compliant joint deformation affects the final assembly precision and should be investigated further under different machining methods.…”
Section: Introductionmentioning
confidence: 99%
“…11 proposed a method to improve the accuracy of the machine tool assembly by considering the deformation of the joint surface and using the antideformation principle. Lu 12 studied the accuracy of the basic parameters of the joint surface on the precision of a CNC machine tool assembly and used a neural network model to predict the final possible assembly accuracy, and found the best assembly sequence. Although these studies considered the joint-surface error as an error source in the machine tool assembly, the roller guide error was less studied.…”
Section: Introductionmentioning
confidence: 99%